The concept of Islamic lifestyle for Muslim tourists - Fadzilah Akmal Haji Ali
Islamic tourism is an emerging market in tourism indu trial with enormous potential but has not been researched in depth for Muslim tourists. Therefore, this research will be based on formulating the problem of how to form a conceptual framework of the Islamic lifestyle for Muslim tourists. This research explores the Islamic tourism lifestyle (ILSMT) from an Islamic perspective through three objectives. The first objective i to identify the concept of ILSMT. The second objective is to analyze the principles and components ofILSMT. The third objective is to establish the conceptual framework of ILSMT. These objectives were achieved through an exploratory qualitative study that identified elements for the concept of ILSMT from an Islamic perspective. Content analysis was used to extract documents and textual sources related to the Islamic lifestyle through a rigorous literature review. This framework was validated through a focus group validation. The expert group participants comprised of academics, Islamic religious councils at the state and national levels, and the tourism indu try. The fmding of the study reveal the Conceptual Framework of ILSMT. The four cor concepts of ILSMT, namely Islamic Tasawwur, Islamic religiosity tAd-din At-Islam), Islamic life (Ad-din Lil-Waq'i) and Islamic consumption. This study shows the components offLSMT, which will be the basis for the formation of monothei m in the personality of Muslim tourists, the concept of compliance with what is allowed and what is forbidden by Allah SWT. This research will allow Muslim tourists to measure various measures in setting the unit of analysis of the study.